The influence of perceived organizational support, human resource practices and leadership styles on turnover intention among generation - Y employees in Selangor manufacturing companies - Mohd Zaid, Mohd Idrus (2017)
Employee turnover is an unavoidable scenario faced by many organizations regardless of it economic sectors. Uncontrollable turnover is very costly for the employer because it encompasses of efforts, times and costs of rehiring, training, and low productivity effects. Turnover intention is found as the strongest predictor for actual turnover in previous studies. Due to high turnover ratio among manufacturing workers in Malaysia, it demands great concern and some understandings on turnover intention subject. This research investigated the causes that triggering workers’ intention to leave towards their current company. In this regard, this study tries to determine the significance relationships of perceived organizational support, human resource practices and leadership styles on turnover intention among generation Y employees in Selangor manufacturing companies. Data were gathered using questionnaires collected from 200 local employees in various manufacturing companies in Selangor. Hypothesis for direct effect were tested using correlation and regression analyses. Results showed that only leadership styles which are transformational leadership style, transactional leadership style (management by exception passive) and laissez-faire leadership style were significantly associated with employee’s turnover intention. Implications of the findings, potential limitations, and directions for future research are discussed.